Implement zip using foldr - haskell

I'm currently on chapter 4 of Real World Haskell, and I'm trying to wrap my head around implementing foldl in terms of foldr.
(Here's their code:)
myFoldl :: (a -> b -> a) -> a -> [b] -> a
myFoldl f z xs = foldr step id xs z
where step x g a = g (f a x)
I thought I'd try to implement zip using the same technique, but I don't seem to be making any progress. Is it even possible?

zip2 xs ys = foldr step done xs ys
where done ys = []
step x zipsfn [] = []
step x zipsfn (y:ys) = (x, y) : (zipsfn ys)
How this works: (foldr step done xs) returns a function that consumes
ys; so we go down the xs list building up a nested composition of
functions that will each be applied to the corresponding part of ys.
How to come up with it: I started with the general idea (from similar
examples seen before), wrote
zip2 xs ys = foldr step done xs ys
then filled in each of the following lines in turn with what it had to
be to make the types and values come out right. It was easiest to
consider the simplest cases first before the harder ones.
The first line could be written more simply as
zip2 = foldr step done
as mattiast showed.

The answer had already been given here, but not an (illustrative) derivation. So even after all these years, perhaps it's worth adding it.
It is actually quite simple. First,
foldr f z xs
= foldr f z [x1,x2,x3,...,xn] = f x1 (foldr f z [x2,x3,...,xn])
= ... = f x1 (f x2 (f x3 (... (f xn z) ...)))
hence by eta-expansion,
foldr f z xs ys
= foldr f z [x1,x2,x3,...,xn] ys = f x1 (foldr f z [x2,x3,...,xn]) ys
= ... = f x1 (f x2 (f x3 (... (f xn z) ...))) ys
As is apparent here, if f is non-forcing in its 2nd argument, it gets to work first on x1 and ys, f x1r1ys where r1 =(f x2 (f x3 (... (f xn z) ...)))= foldr f z [x2,x3,...,xn].
So, using
f x1 r1 [] = []
f x1 r1 (y1:ys1) = (x1,y1) : r1 ys1
we arrange for passage of information left-to-right along the list, by calling r1 with the rest of the input list ys1, foldr f z [x2,x3,...,xn]ys1 = f x2r2ys1, as the next step. And that's that.
When ys is shorter than xs (or the same length), the [] case for f fires and the processing stops. But if ys is longer than xs then f's [] case won't fire and we'll get to the final f xnz(yn:ysn) application,
f xn z (yn:ysn) = (xn,yn) : z ysn
Since we've reached the end of xs, the zip processing must stop:
z _ = []
And this means the definition z = const [] should be used:
zip xs ys = foldr f (const []) xs ys
where
f x r [] = []
f x r (y:ys) = (x,y) : r ys
From the standpoint of f, r plays the role of a success continuation, which f calls when the processing is to continue, after having emitted the pair (x,y).
So r is "what is done with more ys when there are more xs", and z = const [], the nil-case in foldr, is "what is done with ys when there are no more xs". Or f can stop by itself, returning [] when ys is exhausted.
Notice how ys is used as a kind of accumulating value, which is passed from left to right along the list xs, from one invocation of f to the next ("accumulating" step being, here, stripping a head element from it).
Naturally this corresponds to the left fold, where an accumulating step is "applying the function", with z = id returning the final accumulated value when "there are no more xs":
foldl f a xs =~ foldr (\x r a-> r (f a x)) id xs a
Similarly, for finite lists,
foldr f a xs =~ foldl (\r x a-> r (f x a)) id xs a
And since the combining function gets to decide whether to continue or not, it is now possible to have left fold that can stop early:
foldlWhile t f a xs = foldr cons id xs a
where
cons x r a = if t x then r (f a x) else a
or a skipping left fold, foldlWhen t ..., with
cons x r a = if t x then r (f a x) else r a
etc.

I found a way using quite similar method to yours:
myzip = foldr step (const []) :: [a] -> [b] -> [(a,b)]
where step a f (b:bs) = (a,b):(f bs)
step a f [] = []

For the non-native Haskellers here, I've written a Scheme version of this algorithm to make it clearer what's actually happening:
> (define (zip lista listb)
((foldr (lambda (el func)
(lambda (a)
(if (empty? a)
empty
(cons (cons el (first a)) (func (rest a))))))
(lambda (a) empty)
lista) listb))
> (zip '(1 2 3 4) '(5 6 7 8))
(list (cons 1 5) (cons 2 6) (cons 3 7) (cons 4 8))
The foldr results in a function which, when applied to a list, will return the zip of the list folded over with the list given to the function. The Haskell hides the inner lambda because of lazy evaluation.
To break it down further:
Take zip on input: '(1 2 3)
The foldr func gets called with
el->3, func->(lambda (a) empty)
This expands to:
(lambda (a) (cons (cons el (first a)) (func (rest a))))
(lambda (a) (cons (cons 3 (first a)) ((lambda (a) empty) (rest a))))
If we were to return this now, we'd have a function which takes a list of one element
and returns the pair (3 element):
> (define f (lambda (a) (cons (cons 3 (first a)) ((lambda (a) empty) (rest a)))))
> (f (list 9))
(list (cons 3 9))
Continuing, foldr now calls func with
el->3, func->f ;using f for shorthand
(lambda (a) (cons (cons el (first a)) (func (rest a))))
(lambda (a) (cons (cons 2 (first a)) (f (rest a))))
This is a func which takes a list with two elements, now, and zips them with (list 2 3):
> (define g (lambda (a) (cons (cons 2 (first a)) (f (rest a)))))
> (g (list 9 1))
(list (cons 2 9) (cons 3 1))
What's happening?
(lambda (a) (cons (cons 2 (first a)) (f (rest a))))
a, in this case, is (list 9 1)
(cons (cons 2 (first (list 9 1))) (f (rest (list 9 1))))
(cons (cons 2 9) (f (list 1)))
And, as you recall, f zips its argument with 3.
And this continues etc...

The problem with all these solutions for zip is that they only fold over one list or the other, which can be a problem if both of them are "good producers", in the parlance of list fusion. What you actually need is a solution that folds over both lists. Fortunately, there is a paper about exactly that, called "Coroutining Folds with Hyperfunctions".
You need an auxiliary type, a hyperfunction, which is basically a function that takes another hyperfunction as its argument.
newtype H a b = H { invoke :: H b a -> b }
The hyperfunctions used here basically act like a "stack" of ordinary functions.
push :: (a -> b) -> H a b -> H a b
push f q = H $ \k -> f $ invoke k q
You also need a way to put two hyperfunctions together, end to end.
(.#.) :: H b c -> H a b -> H a c
f .#. g = H $ \k -> invoke f $ g .#. k
This is related to push by the law:
(push f x) .#. (push g y) = push (f . g) (x .#. y)
This turns out to be an associative operator, and this is the identity:
self :: H a a
self = H $ \k -> invoke k self
You also need something that disregards everything else on the "stack" and returns a specific value:
base :: b -> H a b
base b = H $ const b
And finally, you need a way to get a value out of a hyperfunction:
run :: H a a -> a
run q = invoke q self
run strings all of the pushed functions together, end to end, until it hits a base or loops infinitely.
So now you can fold both lists into hyperfunctions, using functions that pass information from one to the other, and assemble the final value.
zip xs ys = run $ foldr (\x h -> push (first x) h) (base []) xs .#. foldr (\y h -> push (second y) h) (base Nothing) ys where
first _ Nothing = []
first x (Just (y, xys)) = (x, y):xys
second y xys = Just (y, xys)
The reason why folding over both lists matters is because of something GHC does called list fusion, which is talked about in the GHC.Base module, but probably should be much more well-known. Being a good list producer and using build with foldr can prevent lots of useless production and immediate consumption of list elements, and can expose further optimizations.

I tried to understand this elegant solution myself, so I tried to derive the types and evaluation myself. So, we need to write a function:
zip xs ys = foldr step done xs ys
Here we need to derive step and done, whatever they are. Recall foldr's type, instantiated to lists:
foldr :: (a -> state -> state) -> state -> [a] -> state
However our foldr invocation must be instantiated to something like below, because we must accept not one, but two list arguments:
foldr :: (a -> ? -> ?) -> ? -> [a] -> [b] -> [(a,b)]
Because -> is right-associative, this is equivalent to:
foldr :: (a -> ? -> ?) -> ? -> [a] -> ([b] -> [(a,b)])
Our ([b] -> [(a,b)]) corresponds to state type variable in the original foldr type signature, therefore we must replace every occurrence of state with it:
foldr :: (a -> ([b] -> [(a,b)]) -> ([b] -> [(a,b)]))
-> ([b] -> [(a,b)])
-> [a]
-> ([b] -> [(a,b)])
This means that arguments that we pass to foldr must have the following types:
step :: a -> ([b] -> [(a,b)]) -> [b] -> [(a,b)]
done :: [b] -> [(a,b)]
xs :: [a]
ys :: [b]
Recall that foldr (+) 0 [1,2,3] expands to:
1 + (2 + (3 + 0))
Therefore if xs = [1,2,3] and ys = [4,5,6,7], our foldr invocation would expand to:
1 `step` (2 `step` (3 `step` done)) $ [4,5,6,7]
This means that our 1 `step` (2 `step` (3 `step` done)) construct must create a recursive function that would go through [4,5,6,7] and zip up the elements. (Keep in mind, that if one of the original lists is longer, the excess values are thrown away). IOW, our construct must have the type [b] -> [(a,b)].
3 `step` done is our base case, where done is an initial value, like 0 in foldr (+) 0 [1..3]. We don't want to zip anything after 3, because 3 is the final value of xs, so we must terminate the recursion. How do you terminate the recursion over list in the base case? You return empty list []. But recall done type signature:
done :: [b] -> [(a,b)]
Therefore we can't return just [], we must return a function that would ignore whatever it receives. Therefore use const:
done = const [] -- this is equivalent to done = \_ -> []
Now let's start figuring out what step should be. It combines a value of type a with a function of type [b] -> [(a,b)] and returns a function of type [b] -> [(a,b)].
In 3 `step` done, we know that the result value that would later go to our zipped list must be (3,6) (knowing from original xs and ys). Therefore 3 `step` done must evaluate into:
\(y:ys) -> (3,y) : done ys
Remember, we must return a function, inside which we somehow zip up the elements, the above code is what makes sense and typechecks.
Now that we assumed how exactly step should evaluate, let's continue the evaluation. Here's how all reduction steps in our foldr evaluation look like:
3 `step` done -- becomes
(\(y:ys) -> (3,y) : done ys)
2 `step` (\(y:ys) -> (3,y) : done ys) -- becomes
(\(y:ys) -> (2,y) : (\(y:ys) -> (3,y) : done ys) ys)
1 `step` (\(y:ys) -> (2,y) : (\(y:ys) -> (3,y) : done ys) ys) -- becomes
(\(y:ys) -> (1,y) : (\(y:ys) -> (2,y) : (\(y:ys) -> (3,y) : done ys) ys) ys)
The evaluation gives rise to this implementation of step (note that we account for ys running out of elements early by returning an empty list):
step x f = \[] -> []
step x f = \(y:ys) -> (x,y) : f ys
Thus, the full function zip is implemented as follows:
zip :: [a] -> [b] -> [(a,b)]
zip xs ys = foldr step done xs ys
where done = const []
step x f [] = []
step x f (y:ys) = (x,y) : f ys
P.S.: If you are inspired by elegance of folds, read Writing foldl using foldr and then Graham Hutton's A tutorial on the universality and expressiveness of fold.

A simple approach:
lZip, rZip :: Foldable t => [b] -> t a -> [(a, b)]
-- implement zip using fold?
lZip xs ys = reverse.fst $ foldl f ([],xs) ys
where f (zs, (y:ys)) x = ((x,y):zs, ys)
-- Or;
rZip xs ys = fst $ foldr f ([],reverse xs) ys
where f x (zs, (y:ys)) = ((x,y):zs, ys)

Related

Why is it sometimes possible to fold an infinite list from the right?

I have been going through the excellent CIS 194 course when I got stuck on Part 5 of Homework 6. It revolves around implementing the ruler function without any divisibility testing.
I found that it is possible to build the ruler function by continuously interspersing an accumulator with values from an infinite list.
nats = [0,1,2,3,..]
[3]
[2,3,2]
[1,2,1,3,1,2,1]
[0,1,0,2,0,1,0,3,0,1,0,2,0]
Then I tried implementing this algorithm for Stream datatype which is a list without nil
data Stream a = Cons a (Stream a)
streamToList :: Stream a -> [a]
streamToList (Cons x xs) = x : streamToList xs
instance Show a => Show (Stream a) where
show = show . take 20 . streamToList
streamFromSeed :: (a -> a) -> a -> Stream a
streamFromSeed f x = Cons x (streamFromSeed f (f x))
nats :: Stream Integer
nats = streamFromSeed succ 0
interleave x (Cons y ys) = Cons x (Cons y (interleave x ys))
foldStream f (Cons x xs) = f x (foldStream f xs)
ruler = foldStream interleave nats
As expected, I got stackoverflow error since I was trying to fold from the right. However, I was surprised to see the same algorithm work for normal infinite lists.
import Data.List
interleave x list = [x] ++ (intersperse x list) ++ [x]
ruler = take 20 (foldr interleave [] [0..])
What am I missing? Why one implementation works while the other doesn't?
Your interleave is insufficiently lazy. The magic thing that right folds must do to work on infinite structures is to not inspect the result of the folded value too closely before they do the first bit of computation. So:
interleave x stream = Cons x $ case stream of
Cons y ys -> Cons y (interleave x ys)
This produces Cons x _ before inspecting stream; in contrast, your version requires stream to be evaluated a bit before it can pass to the right hand side of the equation, which essentially forces the entire fold to happen before any constructor gets produced.
You can also see this in your list version of interleave:
interleave x list = [x] ++ intersperse x list ++ [x]
The first element of the returned list (x) is known before intersperse starts pattern matching on list.
We can inspect the source code of foldr [src]. A less noisy version looks like:
foldr f z [] = z
foldr f z (x:xs) = f x (foldr f z xs)
Haskell does not evaluate eagerly. This thus means that, unless you need (foldr f z xs), it will not evaluate the accumulator. This thus means that f does not need the second parameter, for example because the first item x has a certain value, it will not evaluate the accumulator.
For example if we implement takeWhileNeq:
takeWhileNeq a = foldr f []
where f x xs -> if x == a then [] else (x:xs)
if we thus run this on a list takeWhileNeq 2 [1,4,2,5], then it will not evaluate anything. If we however want to print the result it will evaluate this as:
f 1 (foldr f [4,2,5])
and f will inspect if 1 == 2, since that is not the case, it will return (x:xs), so:
-> 1 : foldr f [4,2,5]
so now it will evaluate 4 == 2, and because this is false, it will evaluate this to:
-> 1 : (4 : foldr f [2,5])
now we evaluate 2 == 2, and since this is True, the function returns the empty list, and ingores the accumulator, so it will never look at foldr f [5]:
-> 1 : (4 : [])
For an infinite list, it will thus also result an empty list and ignore folding the rest of the list.

Can my implementation of filter be improved?

An exercise in Haskell from First Principles says to implement filter using foldr and this is what I came up with but it feels and looks clunky. Is there a more natural way to implement it with a foldr?
import Data.Bool
myFilter :: (a -> Bool) -> [a] -> [a]
myFilter f = foldr (\x -> bool (++ []) ((:) x) (f x)) []
I would only use bool if it let me get rid of the lambda expression simply, by composing a call to bool with the predicate p: bool iffalse iftrue . p. However, p isn't the only function that needs to be called on a list element; (:) does as well. You could use the Applicative instance for functions, to write
myfilter p = foldr (bool id . (:) <*> p) [] -- yuck
but in this case I would just use a plain if expression, inside the lambda expression:
myfilter p = foldr (\x -> if p x then (x:) else id) [] -- much clearer!
Note that when specialized to functions, the Applicative's (<*>) operator is defined as f <*> g = \x -> f x (g x). I leave it as an exercise to use that definition to transform bool id . (:) <*> p into
\x -> bool id (x:) (p x).
You can use the Applicative instance of (->) a to make the lambda cleaner. But, if you want to use foldr, I don't think there's any substantial change you can effect:
myFilter f = foldr (bool id <$> (:) <*> f) []
bool id <$> (:) <*> f means \x -> bool id ((:) x) (f x). bool id has type ([a] -> [a]) -> Bool -> ([a] -> [a]). (:) has type a -> [a] -> [a], and f has type a -> Bool. When (<$>) and (<*>) are used in this way, you can think of it as pretending that (:) and f don't have an a argument, making them [a] -> [a] and Bool, respectively, applying them to bool id to get a [a] -> [a], and then ending the lie by reintroducing the a argument, making a a -> [a] -> [a]. The operators are in charge of threading that a around, so you don't need a lambda abstraction.
Rather than merely searching for a more elegant implementation, it would might help you more to learn an elegant process of searching for an implementation. This should make it simpler to find elegant solutions.
For any function h on lists we have that,
h = foldr f e
if and only if
h [] = e
h (x:xs) = f x (h xs)
In this case your h is filter p for some boolean function p that selects which elements to keep. Implementing filter p as a "simple" recursive function is not too hard.
filter p [] = []
filter p (x:xs) = if p x then x : (filter p xs) else (filter p xs)
The 1st line implies e = []. The 2nd line needs to be written in the form f x (filter p xs) to match the equation of h above, in order for us to deduce which f to plug in the foldr. To do that we just abstract over those two expressions.
filter p [] = []
filter p (x:xs) = (\x ys -> if p x then x : ys else ys) x (filter p xs)
So we have found that,
e = []
f x ys = if p x then x: ys else ys
It therefore follows,
filter p = foldr (\y ys -> if p y then y : ys else ys) []
To learn more about this method of working with foldr I recommend reading
"A tutorial on the universality and expressiveness of fold" by Graham Hutton.
Some added notes:
In case this seems overly complicated, note that while the principles above can be used in this "semi rigorous" fashion via algebraic manipulation, they can and should also be used to guide your intuition and aid you in informal development.
The equation for h (x:xs) = f x (h xs) sheds some clarity on how to find f. In the case where h is the filtering function you want an f which combines the element x with a tail that has already been filtered. If you really understand this it should be easy to arrive at,
f x ys = if p x then x : ys else ys
Yes, there is:
myFilter :: (a -> Bool) -> [a] -> [a]
myFilter f = foldMap (\x -> [x | f x])
> myFilter even [1..10]
[2,4,6,8,10]
See, I switched it on you, with foldMap.
Well, with foldr it is foldr (\x -> ([x | f x] ++)) [].

foldl . foldr function composition - Haskell

So, I'm really frying my brain trying do understand the foldl.foldr composition.
Here is a example:
(foldl.foldr) (+) 1 [[1,2,3],[4,5,6]]
The result is 22, but what's really happening here?
To me it looks like this is what is happening: foldl (+) 1 [6,15].
My doubt is related to the foldr part. Shouldn't it add the 1 to all the sub-lists? Like this: foldr (+) 1 [1,2,3].
In my head the 1 is added just one time, is it right? (probably not, but I want to know how/why!).
I'm very confused (and perhaps making all the confusion, haha).
Thank you!
(foldl.foldr) (+) 1 [[1,2,3],[4,5,6]]
becomes
foldl (foldr (+)) 1 [[1,2,3],[4,5,6]]
So you get
foldl (foldr (+)) (foldr (+) 1 [1,2,3]) [[4,5,6]]
after the first step of foldl, or
foldl (foldr (+)) 7 [[4,5,6]]
if we evaluate the applied foldr (unless the strictness analyser kicks in, it would in reality remain an unevaluated thunk until the foldl has traversed the entire list, but the next expression is more readable with it evaluated), and that becomes
foldl (foldr (+)) (foldr (+) 7 [4,5,6]) []
and finally
foldl (foldr (+)) 22 []
~> 22
Let's examine foldl . foldr. Their types are
foldl :: (a -> b -> a) -> (a -> [b] -> a)
foldr :: (c -> d -> d) -> (d -> [c] -> d)
I intentionally used distinct type variables and I added parentheses so that it becomes more apparent that we view them now as functions of one argument (and their results are functions). Looking at foldl we see that it is a kind of lifting function: Given a function that produces a from a using b, we lift it so that it works on [b] (by repeating the computation). Function foldr is similar, just with arguments reversed.
Now what happens if we apply foldl . foldr? First, let's derive the type: We have to unify the type variables so that the result of foldr matches the argument of foldl. So we have to substitute: a = d, b = [c]:
foldl :: (d -> [c] -> d) -> (d -> [[c]] -> d)
foldr :: (c -> d -> d) -> (d -> [c] -> d)
So we get
foldl . foldr :: (c -> d -> d) -> (d -> [[c]] -> d)
And what is its meaning? First, foldr lifts the argument of type c -> d -> d to work on lists, and reverses its arguments so that we get d -> [c] -> d. Next, foldl lifts this function again to work on [[c]] - lists of [c].
In your case, the operation being lifted (+) is associative, so we don't have care about the order of its application. The double lifting simply creates a function that applies the operation on all the nested elements.
If we use just foldl, the effect is even nicer: We can lift multiple times, like in
foldl . foldl . foldl . foldl
:: (a -> b -> a) -> (a -> [[[[b]]]] -> a)
Actually, (foldl.foldr) f z xs === foldr f z (concat $ reverse xs).
Even if f is an associative operation, the correct sequence of applications matters, as it can have an impact on performance.
We begin with
(foldl.foldr) f z xs
foldl (foldr f) z xs
writing with g = foldr f and [x1,x2,...,xn_1,xn] = xs for a moment, this is
(...((z `g` x1) `g` x2) ... `g` xn)
(`g` xn) ((`g` xn_1) ... ((`g` x1) z) ... )
foldr f z $ concat [xn,xn_1, ..., x1]
foldr f z $ concat $ reverse xs
So in your case the correct reduction sequence is
(foldl.foldr) 1 [[1,2,3],[4,5,6]]
4+(5+(6+( 1+(2+(3+ 1)))))
22
To wit,
Prelude> (foldl.foldr) (:) [] [[1..3],[4..6],[7..8]]
[7,8,4,5,6,1,2,3]
Similarly, (foldl.foldl) f z xs == foldl f z $ concat xs. With snoc a b = a++[b],
Prelude> (foldl.foldl) snoc [] [[1..3],[4..6],[7..8]]
[1,2,3,4,5,6,7,8]
Also, (foldl.foldl.foldl) f z xs == (foldl.foldl) (foldl f) z xs == foldl (foldl f) z $ concat xs == (foldl.foldl) f z $ concat xs == foldl f z $ concat (concat xs), etc.:
Prelude> (foldl.foldl.foldl) snoc [] [[[1..3],[4..6]],[[7..8]]]
[1,2,3,4,5,6,7,8]
Prelude> (foldl.foldr.foldl) snoc [] [[[1..3],[4..6]],[[7..8]]]
[7,8,1,2,3,4,5,6]
Prelude> (foldl.foldl.foldr) (:) [] [[[1..3],[4..6]],[[7..8]]]
[7,8,4,5,6,1,2,3]

Church lists in Haskell

I had to implement the haskell map function to work with church lists which are defined as following:
type Churchlist t u = (t->u->u)->u->u
In lambda calculus, lists are encoded as following:
[] := λc. λn. n
[1,2,3] := λc. λn. c 1 (c 2 (c 3 n))
The sample solution of this exercise is:
mapChurch :: (t->s) -> (Churchlist t u) -> (Churchlist s u)
mapChurch f l = \c n -> l (c.f) n
I have NO idea how this solution works and I don't know how to create such a function. I have already experience with lambda calculus and church numerals, but this exercise has been a big headache for me and I have to be able to understand and solve such problems for my exam next week. Could someone please give me a good source where I could learn to solve such problems or give me a little guidance on how it works?
All lambda calculus data structures are, well, functions, because that's all there is in the lambda calculus. That means that the representation for a boolean, tuple, list, number, or anything, has to be some function that represents the active behavior of that thing.
For lists, it is a "fold". Immutable singly-linked lists are usually defined List a = Cons a (List a) | Nil, meaning the only ways you can construct a list is either Nil or Cons anElement anotherList. If you write it out in lisp-style, where c is Cons and n is Nil, then the list [1,2,3] looks like this:
(c 1 (c 2 (c 3 n)))
When you perform a fold over a list, you simply provide your own "Cons" and "Nil" to replace the list ones. In Haskell, the library function for this is foldr
foldr :: (a -> b -> b) -> b -> [a] -> b
Look familiar? Take out the [a] and you have the exact same type as Churchlist a b. Like I said, church encoding represents lists as their folding function.
So the example defines map. Notice how l is used as a function: it is the function that folds over some list, after all. \c n -> l (c.f) n basically says "replace every c with c . f and every n with n".
(c 1 (c 2 (c 3 n)))
-- replace `c` with `(c . f)`, and `n` with `n`
((c . f) 1 ((c . f) 2) ((c . f) 3 n)))
-- simplify `(foo . bar) baz` to `foo (bar baz)`
(c (f 1) (c (f 2) (c (f 3) n))
It should be apparent now that this is indeed a mapping function, because it looks just like the original, except 1 turned into (f 1), 2 to (f 2), and 3 to (f 3).
So let's start by encoding the two list constructors, using your example as reference:
[] := λc. λn. n
[1,2,3] := λc. λn. c 1 (c 2 (c 3 n))
[] is the end of list constructor, and we can lift that straight from the example. [] already has meaning in haskell, so let's call ours nil:
nil = \c n -> n
The other constructor we need takes an element and an existing list, and creates a new list. Canonically, this is called cons, with the definition:
cons x xs = \c n -> c x (xs c n)
We can check that this is consistent with the example above, since
cons 1 (cons 2 (cons 3 nil))) =
cons 1 (cons 2 (cons 3 (\c n -> n)) =
cons 1 (cons 2 (\c n -> c 3 ((\c' n' -> n') c n))) =
cons 1 (cons 2 (\c n -> c 3 n)) =
cons 1 (\c n -> c 2 ((\c' n' -> c' 3 n') c n) ) =
cons 1 (\c n -> c 2 (c 3 n)) =
\c n -> c 1 ((\c' n' -> c' 2 (c' 3 n')) c n) =
\c n -> c 1 (c 2 (c 3 n)) =
Now, consider the purpose of the map function - it is to apply the given function to each element of the list. So let's see how that works for each of the constructors.
nil has no elements, so mapChurch f nil should just be nil:
mapChurch f nil
= \c n -> nil (c.f) n
= \c n -> (\c' n' -> n') (c.f) n
= \c n -> n
= nil
cons has an element and a rest of list, so, in order for mapChurch f to work propery, it must apply f to the element and mapChurch f to rest of the list. That is, mapChurch f (cons x xs) should be the same as cons (f x) (mapChurch f xs).
mapChurch f (cons x xs)
= \c n -> (cons x xs) (c.f) n
= \c n -> (\c' n' -> c' x (xs c' n')) (c.f) n
= \c n -> (c.f) x (xs (c.f) n)
-- (c.f) x = c (f x) by definition of (.)
= \c n -> c (f x) (xs (c.f) n)
= \c n -> c (f x) ((\c' n' -> xs (c'.f) n') c n)
= \c n -> c (f x) ((mapChurch f xs) c n)
= cons (f x) (mapChurch f xs)
So since all lists are made from those two constructors, and mapChurch works on both of them as expected, mapChurch must work as expected on all lists.
Well, we can comment the Churchlist type this way to clarify it:
-- Tell me...
type Churchlist t u = (t -> u -> u) -- ...how to handle a pair
-> u -- ...and how to handle an empty list
-> u -- ...and then I'll transform a list into
-- the type you want
Note that this is intimately related to the foldr function:
foldr :: (t -> u -> u) -> u -> [t] -> u
foldr k z [] = z
foldr k z (x:xs) = k x (foldr k z xs)
foldr is a very general function that can implement all sorts of other list functions. A trivial example that will help you is implementing a list copy with foldr:
copyList :: [t] -> [t]
copyList xs = foldr (:) [] xs
Using the commented type above, foldr (:) [] means this: "if you see an empty list return the empty list, and if you see a pair return head:tailResult."
Using Churchlist, you can easily write the counterpart this way:
-- Note that the definitions of nil and cons mirror the two foldr equations!
nil :: Churchlist t u
nil = \k z -> z
cons :: t -> Churchlist t u -> Churchlist t u
cons x xs = \k z -> k x (xs k z)
copyChurchlist :: ChurchList t u -> Churchlist t u
copyChurchlist xs = xs cons nil
Now, to implement map, you just need to replace cons with a suitable function, like this:
map :: (a -> b) -> [a] -> [b]
map f xs = foldr (\x xs' -> f x:xs') [] xs
Mapping is like copying a list, except that instead of just copying the elements verbatim you apply f to each of them.
Study all of this carefully, and you should be able to write mapChurchlist :: (t -> t') -> Churchlist t u -> Churchlist t' u on your own.
Extra exercise (easy): write these list functions in terms of foldr, and write counterparts for Churchlist:
filter :: (a -> Bool) -> [a] -> [a]
append :: [a] -> [a] -> [a]
-- Return first element of list that satisfies predicate, or Nothing
find :: (a -> Bool) -> [a] -> Maybe a
If you're feeling like tackling something harder, try writing tail for Churchlist. (Start by writing tail for [a] using foldr.)

Writing foldl using foldr

In Real World Haskell, Chapter 4. on Functional Programming:
Write foldl with foldr:
-- file: ch04/Fold.hs
myFoldl :: (a -> b -> a) -> a -> [b] -> a
myFoldl f z xs = foldr step id xs z
where step x g a = g (f a x)
The above code confused me a lot, and somebody called dps rewrote it with a meaningful name to make it a bit clearer:
myFoldl stepL zeroL xs = (foldr stepR id xs) zeroL
where stepR lastL accR accInitL = accR (stepL accInitL lastL)
Somebody else, Jef G, then did an excellent job by providing an example and showing the underlying mechanism step by step:
myFoldl (+) 0 [1, 2, 3]
= (foldR step id [1, 2, 3]) 0
= (step 1 (step 2 (step 3 id))) 0
= (step 1 (step 2 (\a3 -> id ((+) a3 3)))) 0
= (step 1 (\a2 -> (\a3 -> id ((+) a3 3)) ((+) a2 2))) 0
= (\a1 -> (\a2 -> (\a3 -> id ((+) a3 3)) ((+) a2 2)) ((+) a1 1)) 0
= (\a1 -> (\a2 -> (\a3 -> (+) a3 3) ((+) a2 2)) ((+) a1 1)) 0
= (\a1 -> (\a2 -> (+) ((+) a2 2) 3) ((+) a1 1)) 0
= (\a1 -> (+) ((+) ((+) a1 1) 2) 3) 0
= (+) ((+) ((+) 0 1) 2) 3
= ((0 + 1) + 2) + 3
But I still cannot fully understand that, here are my questions:
What is the id function for? What is the role of? Why should we need it here?
In the above example, id function is the accumulator in the lambda function?
foldr's prototype is foldr :: (a -> b -> b) -> b -> [a] -> b, and the first parameter is a function which need two parameters, but the step function in the myFoldl's implementation uses 3 parameters, I'm complelely confused!
Some explanations are in order!
What is the id function for? What is the role of? Why should we need it here?
id is the identity function, id x = x, and is used as the equivalent of zero when building up a chain of functions with function composition, (.). You can find it defined in the Prelude.
In the above example, id function is the accumulator in the lambda function?
The accumulator is a function that is being built up via repeated function application. There's no explicit lambda, since we name the accumulator, step. You can write it with a lambda if you want:
foldl f a bs = foldr (\b g x -> g (f x b)) id bs a
Or as Graham Hutton would write:
5.1 The foldl operator
Now let us generalise from the suml example and consider the standard operator foldl that processes the elements of a list in left-to-right order by using a function f to combine values, and a value v as the starting value:
foldl :: (β → α → β) → β → ([α] → β)
foldl f v [ ] = v
foldl f v (x : xs) = foldl f (f v x) xs
Using this operator, suml can be redefined simply by suml = foldl (+) 0. Many other functions can be defined in a simple way using foldl. For example, the standard function reverse can redefined using foldl as follows:
reverse :: [α] → [α]
reverse = foldl (λxs x → x : xs) [ ]
This definition is more efficient than our original definition using fold, because it avoids the use of the inefficient append operator (++) for lists.
A simple generalisation of the calculation in the previous section for the function suml shows how to redefine the function foldl in terms of fold:
foldl f v xs = fold (λx g → (λa → g (f a x))) id xs v
In contrast, it is not possible to redefine fold in terms of foldl, due to the fact that
foldl is strict in the tail of its list argument but fold is not. There are a number of useful ‘duality theorems’ concerning fold and foldl, and also some guidelines for deciding which operator is best suited to particular applications (Bird, 1998).
foldr's prototype is foldr :: (a -> b -> b) -> b -> [a] -> b
A Haskell programmer would say that the type of foldr is (a -> b -> b) -> b -> [a] -> b.
and the first parameter is a function which need two parameters, but the step function in the myFoldl's implementation uses 3 parameters, I'm complelely confused
This is confusing and magical! We play a trick and replace the accumulator with a function, which is in turn applied to the initial value to yield a result.
Graham Hutton explains the trick to turn foldl into foldr in the above article. We start by writing down a recursive definition of foldl:
foldl :: (a -> b -> a) -> a -> [b] -> a
foldl f v [] = v
foldl f v (x : xs) = foldl f (f v x) xs
And then refactor it via the static argument transformation on f:
foldl :: (a -> b -> a) -> a -> [b] -> a
foldl f v xs = g xs v
where
g [] v = v
g (x:xs) v = g xs (f v x)
Let's now rewrite g so as to float the v inwards:
foldl f v xs = g xs v
where
g [] = \v -> v
g (x:xs) = \v -> g xs (f v x)
Which is the same as thinking of g as a function of one argument, that returns a function:
foldl f v xs = g xs v
where
g [] = id
g (x:xs) = \v -> g xs (f v x)
Now we have g, a function that recursively walks a list, apply some function f. The final value is the identity function, and each step results in a function as well.
But, we have handy already a very similar recursive function on lists, foldr!
2 The fold operator
The fold operator has its origins in recursion theory (Kleene, 1952), while the use
of fold as a central concept in a programming language dates back to the reduction operator of APL (Iverson, 1962), and later to the insertion operator of FP (Backus,
1978). In Haskell, the fold operator for lists can be defined as follows:
fold :: (α → β → β) → β → ([α] → β)
fold f v [ ] = v
fold f v (x : xs) = f x (fold f v xs)
That is, given a function f of type α → β → β and a value v of type β, the function
fold f v processes a list of type [α] to give a value of type β by replacing the nil
constructor [] at the end of the list by the value v, and each cons constructor (:) within the list by the function f. In this manner, the fold operator encapsulates a simple pattern of recursion for processing lists, in which the two constructors for lists are simply replaced by other values and functions. A number of familiar functions on lists have a simple definition using fold.
This looks like a very similar recursive scheme to our g function. Now the trick: using all the available magic at hand (aka Bird, Meertens and Malcolm) we apply a special rule, the universal property of fold, which is an equivalence between two definitions for a function g that processes lists, stated as:
g [] = v
g (x:xs) = f x (g xs)
if and only if
g = fold f v
So, the universal property of folds states that:
g = foldr k v
where g must be equivalent to the two equations, for some k and v:
g [] = v
g (x:xs) = k x (g xs)
From our earlier foldl designs, we know v == id. For the second equation though, we need
to calculate the definition of k:
g (x:xs) = k x (g xs)
<=> g (x:xs) v = k x (g xs) v -- accumulator of functions
<=> g xs (f v x) = k x (g xs) v -- definition of foldl
<= g' (f v x) = k x g' v -- generalize (g xs) to g'
<=> k = \x g' -> (\a -> g' (f v x)) -- expand k. recursion captured in g'
Which, substituting our calculated definitions of k and v yields a
definition of foldl as:
foldl :: (a -> b -> a) -> a -> [b] -> a
foldl f v xs =
foldr
(\x g -> (\a -> g (f v x)))
id
xs
v
The recursive g is replaced with the foldr combinator, and the accumulator becomes a function built via a chain of compositions of f at each element of the list, in reverse order (so we fold left instead of right).
This is definitely somewhat advanced, so to deeply understand this transformation, the universal property of folds, that makes the transformation possible, I recommend Hutton's tutorial, linked below.
References
Haskell Wiki: Foldl as foldr
A tutorial on the universality and expressiveness of fold, Graham Hutton, J. Functional Programming 9 (4): 355–372, July 1999.
Malcolm, G. Algebraic data types and program transformation., PhD thesis, Groningen University.
Consider the type of foldr:
foldr :: (b -> a -> a) -> a -> [b] -> a
Whereas the type of step is something like b -> (a -> a) -> a -> a. Since step is getting passed to foldr, we can conclude that in this case the fold has a type like (b -> (a -> a) -> (a -> a)) -> (a -> a) -> [b] -> (a -> a).
Don't be confused by the different meanings of a in different signatures; it's just a type variable. Also, keep in mind that the function arrow is right associative, so a -> b -> c is the same thing as a -> (b -> c).
So, yes, the accumulator value for the foldr is a function of type a -> a, and the initial value is id. This makes some sense, because id is a function that doesn't do anything--it's the same reason you'd start with zero as the initial value when adding all the values in a list.
As for step taking three arguments, try rewriting it like this:
step :: b -> (a -> a) -> (a -> a)
step x g = \a -> g (f a x)
Does that make it easier to see what's going on? It takes an extra parameter because it's returning a function, and the two ways of writing it are equivalent. Note also the extra parameter after the foldr: (foldr step id xs) z. The part in parentheses is the fold itself, which returns a function, which is then applied to z.
(quickly skim through my answers [1], [2], [3], [4] to make sure you understand Haskell's syntax, higher-order functions, currying, function composition, $ operator, infix/prefix operators, sections and lambdas)
Universal property of fold
A fold is just a codification of certain kinds of recursion. And universality property simply states that, if your recursion conforms to a certain form, it can be transformed into fold according to some formal rules. And conversely, every fold can be transformed into a recursion of that kind. Once again, some recursions can be translated into folds that give exactly the same answer, and some recursions can't, and there is an exact procedure to do that.
Basically, if your recursive function works on lists an looks like on the left, you can transform it to fold one the right, substituting f and v for what actually is there.
g [] = v ⇒
g (x:xs) = f x (g xs) ⇒ g = foldr f v
For example:
sum [] = 0 {- recursion becomes fold -}
sum (x:xs) = x + sum xs ⇒ sum = foldr 0 (+)
Here v = 0 and sum (x:xs) = x + sum xs is equivalent to sum (x:xs) = (+) x (sum xs), therefore f = (+). 2 more examples
product [] = 1
product (x:xs) = x * product xs ⇒ product = foldr 1 (*)
length [] = 0
length (x:xs) = 1 + length xs ⇒ length = foldr (\_ a -> 1 + a) 0
Exercise:
Implement map, filter, reverse, concat and concatMap recursively, just like the above functions on the left side.
Convert these 5 functions to foldr according to a formula above, that is, substituting f and v in the fold formula on the right.
Foldl via foldr
How to write a recursive function that sums numbers up from left to right?
sum [] = 0 -- given `sum [1,2,3]` expands into `(1 + (2 + 3))`
sum (x:xs) = x + sum xs
The first recursive function that comes to find fully expands before even starts adding up, that's not what we need. One approach is to create a recursive function that has accumulator, that immediately adds up numbers on each step (read about tail recursion to learn more about recursion strategies):
suml :: [a] -> a
suml xs = suml' xs 0
where suml' [] n = n -- auxiliary function
suml' (x:xs) n = suml' xs (n+x)
Alright, stop! Run this code in GHCi and make you sure you understand how it works, then carefully and thoughtfully proceed. suml can't be redefined with a fold, but suml' can be.
suml' [] = v -- equivalent: v n = n
suml' (x:xs) n = f x (suml' xs) n
suml' [] n = n from function definition, right? And v = suml' [] from the universal property formula. Together this gives v n = n, a function that immediately returns whatever it receives: v = id. Let's calculate f:
suml' (x:xs) n = f x (suml' xs) n
-- expand suml' definition
suml' xs (n+x) = f x (suml' xs) n
-- replace `suml' xs` with `g`
g (n+x) = f x g n
Thus, suml' = foldr (\x g n -> g (n+x)) id and, thus, suml = foldr (\x g n -> g (n+x)) id xs 0.
foldr (\x g n -> g (n + x)) id [1..10] 0 -- return 55
Now we just need to generalize, replace + by a variable function:
foldl f a xs = foldr (\x g n -> g (n `f` x)) id xs a
foldl (-) 10 [1..5] -- returns -5
Conclusion
Now read Graham Hutton's A tutorial on the universality and expressiveness of fold. Get some pen and paper, try to figure everything that he writes until you get derive most of the folds by yourself. Don't sweat if you don't understand something, you can always return later, but don't procrastinate much either.
Here's my proof that foldl can be expressed in terms of foldr, which I find pretty simple apart from the name spaghetti the step function introduces.
The proposition is that foldl f z xs is equivalent to
myfoldl f z xs = foldr step_f id xs z
where step_f x g a = g (f a x)
The first important thing to notice here is that the right hand side of the first line is actually evaluated as
(foldr step_f id xs) z
since foldr only takes three parameters. This already hints that the foldr will calculate not a value but a curried function, which is then applied to z. There are two cases to investigate to find out whether myfoldl is foldl:
Base case: empty list
myfoldl f z []
= foldr step_f id [] z (by definition of myfoldl)
= id z (by definition of foldr)
= z
foldl f z []
= z (by definition of foldl)
Non-empty list
myfoldl f z (x:xs)
= foldr step_f id (x:xs) z (by definition of myfoldl)
= step_f x (foldr step_f id xs) z (-> apply step_f)
= (foldr step_f id xs) (f z x) (-> remove parentheses)
= foldr step_f id xs (f z x)
= myfoldl f (f z x) xs (definition of myfoldl)
foldl f z (x:xs)
= foldl f (f z x) xs
Since in 2. the first and the last line have the same form in both cases, it can be used to fold the list down until xs == [], in which case 1. guarantees the same result. So by induction, myfoldl == foldl.
There is no Royal Road to Mathematics, nor even through Haskell. Let
h z = (foldr step id xs) z where
step x g = \a -> g (f a x)
What the heck is h z? Assume that xs = [x0, x1, x2].
Apply the definition of foldr:
h z = (step x0 (step x1 (step x2 id))) z
Apply the definition of step:
= (\a0 -> (\a1 -> (\a2 -> id (f a2 x2)) (f a1 x1)) (f a0 x0)) z
Substitute into the lambda functions:
= (\a1 -> (\a2 -> id (f a2 x2)) (f a1 x1)) (f z x0)
= (\a2 -> id (f a2 x2)) (f (f z x0) x1)
= id (f (f (f z x0) x1) x2)
Apply definition of id :
= f (f (f z x0) x1) x2
Apply definition of foldl :
= foldl f z [x0, x1, x2]
Is it a Royal Road or what?
I'm posting the answer for those people who might find this approach better suited to their way of thinking. The answer possibly contains redundant information and thoughts, but it is what I needed in order to tackle the problem. Furthermore, since this is yet another answer to the same question, it's obvious that it has substantial overlaps with the other answers, however it tells the tale of how I could grasp this concept.
Indeed I started to write down this notes as a personal record of my thoughts while trying to understand this topic. It took all the day for me to touch the core of it, if I really have got it.
My long way to understanding this simple exercise
Easy part: what do we need to determine?
What happens with the following example call
foldl f z [1,2,3,4]
can be visualized with the following diagram (which is on Wikipedia, but I first saw it on another answer):
_____results in a number
/
f f (f (f (f z 1) 2) 3) 4
/ \
f 4 f (f (f z 1) 2) 3
/ \
f 3 f (f z 1) 2
/ \
f 2 f z 1
/ \
z 1
(As a side note, when using foldl each applications of f is not performed, and the expressions are thunked just the way I wrote them above; in principle, they could be computed as you go bottom-top, and that's exactly what foldl' does.)
The exercise essentially challenges us to use foldr instead of foldl by appropriately changing the step function (so we use s instead of f) and the initial accumulator (so we use ? instead of z); the list stays the same, otherwise what are we talking about?
The call to foldr has to look like this:
foldr s ? [1,2,3,4]
and the corresponding diagram is this:
_____what does the last call return?
/
s
/ \
1 s
/ \
2 s
/ \
3 s
/ \
4 ? <--- what is the initial accumulator?
The call results in
s 1 (s 2 (s 3 (s 4 ?)))
What are s and ?? And what are their types? It looks like s it's a two argument function, much like f, but let's not jump to conclusions. Also, let's leave ? aside for a moment, and let's observe that z has to come into play as soon as 1 comes into play; however, how can z come into play in the call to the maybe-two-argument s function, namely in the call s 1 (…)? We can solve this part of the enigma by choosing an s which takes 3 arguments, rather than the 2 we mentioned earlier, so that the outermost call s 1 (…) will result in a function taking one argument, which we can pass z to!
This means that we want the original call, which expands to
f (f (f (f z 1) 2) 3) 4
to be equivalent to
s 1 (s 2 (s 3 (s 4 ?))) z
or, in other words, we want the partially applied function
s 1 (s 2 (s 3 (s 4 ?)))
to be equivalent to the following lambda function
(\z -> f (f (f (f z 1) 2) 3) 4)
Again, the "only" pieces we need are s and ?.
Turning point: recognize function composition
Let's redraw the previous diagram and write on the right what we want each call to s be equivalent to:
s s 1 (…) == (\z -> f (f (f (f z 1) 2) 3) 4)
/ \
1 s s 2 (…) == (\z -> f (f (f z 2) 3) 4)
/ \
2 s s 3 (…) == (\z -> f (f z 3) 4)
/ \
3 s s 4 ? == (\z -> f z 4)
/ \
4 ? <--- what is the initial accumulator?
I hope it's clear from the structure of the diagram that the (…) on each line is the right hand side of the line below it; better, it is the function returned from the previous (below) call to s.
It should be also clear that a call to s with arguments x and y is the (full) application of y to the partial application of f to the only argument x (as its second argument). Since the partial application of f to x can be written as the lambda (\z -> f z x), fully applying y to it results in the lambda (\z -> y (f z x)), which in this case I would rewrite as y . (\z -> f z x); translating the words into an expression for s we get
s x y = y . (\z -> f z x)
(This is the same as s x y z = y (f z x), which is the same as the book, if you rename the variables.)
The last bit is: what is the initial "value" ? of the accumulator? The above diagram can be rewritten by expanding the nested calls to make them composition chains:
s s 1 (…) == (\z -> f z 4) . (\z -> f z 3) . (\z -> f z 2) . (\z -> f z 1)
/ \
1 s s 2 (…) == (\z -> f z 4) . (\z -> f z 3) . (\z -> f z 2)
/ \
2 s s 3 (…) == (\z -> f z 4) . (\z -> f z 3)
/ \
3 s s 4 ? == (\z -> f z 4)
/ \
4 ? <--- what is the initial accumulator?
We here see that s simply "piles up" successive partial applications of f, but the y in s x y = y . (\z -> f z x) suggests that the interpretation of s 4 ? (and, in turn, all the others) misses a leading function to be composed with the leftmost lambda.
That's just our ? function: it's time to give it a reason for its existence, beside occupying a place in the call to foldr. What can we choose it to be, in order not to change the resulting functions? Answer: id, the identity function, which is also the identity element with respect to the composition operator (.).
s s 1 (…) == id . (\z -> f z 4) . (\z -> f z 3) . (\z -> f z 2) . (\z -> f z 1)
/ \
1 s s 2 (…) == id . (\z -> f z 4) . (\z -> f z 3) . (\z -> f z 2)
/ \
2 s s 3 (…) == id . (\z -> f z 4) . (\z -> f z 3)
/ \
3 s s 4 id == id . (\z -> f z 4)
/ \
4 id
So the sought function is
myFoldl f z xs = foldr (\x g a -> g (f a x)) id xs z
foldr step zero (x:xs) = step x (foldr step zero xs)
foldr _ zero [] = zero
myFold f z xs = foldr step id xs z
where step x g a = g (f a x)
myFold (+) 0 [1, 2, 3] =
foldr step id [1, 2, 3] 0
-- Expanding foldr function
step 1 (foldr step id [2, 3]) 0
step 1 (step 2 (foldr step id [3])) 0
step 1 (step 2 (step 3 (foldr step id []))) 0
-- Expanding step function if it is possible
step 1 (step 2 (step 3 id)) 0
step 2 (step 3 id) (0 + 1)
step 3 id ((0 + 1) + 2)
id (((0 + 1) + 2) + 3)
Well, at least, this helped me. Even it is not quite right.
This might help, I tried expanding in a different way.
myFoldl (+) 0 [1,2,3] =
foldr step id [1,2,3] 0 =
foldr step (\a -> id (a+3)) [1,2] 0 =
foldr step (\b -> (\a -> id (a+3)) (b+2)) [1] 0 =
foldr step (\b -> id ((b+2)+3)) [1] 0 =
foldr step (\c -> (\b -> id ((b+2)+3)) (c+1)) [] 0 =
foldr step (\c -> id (((c+1)+2)+3)) [] 0 =
(\c -> id (((c+1)+2)+3)) 0 = ...
This answer makes the definition below easily understood in three step.
-- file: ch04/Fold.hs
myFoldl :: (a -> b -> a) -> a -> [b] -> a
myFoldl f z xs = foldr step id xs z
where step x g a = g (f a x)
Step 1. transform the fold of function evaluation to function combination
foldl f z [x1 .. xn] = z & f1 & .. & fn = fn . .. . f1 z. in which fi = \z -> f z xi.
(By using z & f1 & f2 & .. & fn it means fn ( .. (f2 (f1 z)) .. ).)
Step 2. express the function combination in a foldr manner
foldr (.) id [f1 .. fn] = (.) f1 (foldr (.) id [f2 .. fn]) = f1 . (foldr (.) id [f2 .. fn]). Unfold the rest to get foldr (.) id [f1 .. fn] = f1 . .. . fn.
Noticing that the sequence is reversed, we should use the reversed form of (.). Define rc f1 f2 = (.) f2 f1 = f2 . f1, then foldr rc id [f1 .. fn] = rc f1 (foldr (.) id [f2 .. fn]) = (foldr (.) id [f2 .. fn]) . f1. Unfold the rest to get foldr rc id [f1 .. fn] = fn . .. . f1.
Step 3. transform the fold on function list to the fold on operand list
Find step that makes foldr step id [x1 .. xn] = foldr rc id [f1 .. fn]. It is easy to find step = \x g z -> g (f z x).
In 3 steps, the definition of foldl using foldr is clear:
foldl f z xs
= fn . .. . f1 z
= foldr rc id fs z
= foldr step id xs z
Prove the correctness:
foldl f z xs = foldr (\x g z -> g (f z x)) id xs z
= step x1 (foldr step id [x2 .. xn]) z
= s1 (foldr step id [x2 .. xn]) z
= s1 (step x2 (foldr step id [x3 .. xn])) z
= s1 (s2 (foldr step id [x3 .. xn])) z
= ..
= s1 (s2 (.. (sn (foldr step id [])) .. )) z
= s1 (s2 (.. (sn id) .. )) z
= (s2 (.. (sn id) .. )) (f z x1)
= s2 (s3 (.. (sn id) .. )) (f z x1)
= (s3 (.. (sn id) .. )) (f (f z x1) x2)
= ..
= sn id (f (.. (f (f z x1) x2) .. ) xn-1)
= id (f (.. (f (f z x1) x2) .. ) xn)
= f (.. (f (f z x1) x2) .. ) xn
in which xs = [x1 .. xn], si = step xi = \g z -> g (f z xi)
If you find anything to be unclear, please add a comment. :)

Resources